2007
DOI: 10.3354/meps342265
|View full text |Cite
|
Sign up to set email alerts
|

Microhabitat specialisation and ecological consequences for coral gobies of the genus Gobiodon in the Gulf of Aqaba, northern Red Sea

Abstract: The microhabitat selection and distribution of 6 coral-associated species of Gobiodon were examined in the Gulf of Aqaba, northern Red Sea, including 3 recently discovered species. A total of 1626 fishes were counted visually using 10 × 1 m belt transects in 1731 colonies of 13 species of Acropora. Niche segregation was observed at the level of coral species. Gobiodon sp. 2 was the most specialised, occupying only A. hyacinthus; Gobiodon sp. 1 was most generalised (occupying 3 species of Acropora more frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 27 publications
1
43
0
4
Order By: Relevance
“…This pattern also is similar to that of Gobiodon spp. gobies in the northern Red Sea, in which breeding pairs occupy preferred host coral species and non-breeders are relegated to sub-optimal hosts (Dirnwöber & Herler 2007). We observed that pairs of juvenile anemonefish, or 1 juvenile paired with an adult, are uncommon in both anemone hosts, and hypothesize that these occupation patterns are rare because (1) two juvenile fish are unable to fend off adults from an anemone that is sufficiently large to accommodate the juveniles and (2) an adult fish alone may not tolerate the presence of a juvenile, instead preferring to remain alone with extra space available into which another adult may po tentially migrate.…”
Section: Fish and Anemone Population Structurementioning
confidence: 99%
See 2 more Smart Citations
“…This pattern also is similar to that of Gobiodon spp. gobies in the northern Red Sea, in which breeding pairs occupy preferred host coral species and non-breeders are relegated to sub-optimal hosts (Dirnwöber & Herler 2007). We observed that pairs of juvenile anemonefish, or 1 juvenile paired with an adult, are uncommon in both anemone hosts, and hypothesize that these occupation patterns are rare because (1) two juvenile fish are unable to fend off adults from an anemone that is sufficiently large to accommodate the juveniles and (2) an adult fish alone may not tolerate the presence of a juvenile, instead preferring to remain alone with extra space available into which another adult may po tentially migrate.…”
Section: Fish and Anemone Population Structurementioning
confidence: 99%
“…As members of the A. clarkii complex of anemonefishes (Allen 1972), A. bicinctus also may be highly mobile and thus able to migrate easily to Entacmaea quadricolor if space becomes available after growing large enough in Heteractis crispa. This habitat-switch strategy is used by coral gobies (Dirnwöber & Herler 2007), but contrasts with that of less mobile anemonefishes such as A. percula (not in the A. clarkii complex; Elliott et al 1999), in which conspecifics settle into adult habitats and form queues of juveniles leading to the inheritance of a breeding position (Buston 2004). (2) A second possible cause of lower mobility by juvenile than adult A. bicinctus may be aggression by adults, which oust smaller fish that attempt to migrate to an anemone, and prevent them from remaining in preferred anemones.…”
Section: Fish Movement and Host Preferencementioning
confidence: 99%
See 1 more Smart Citation
“…For morphometric analysis of fishes, we collected a total of 93 juvenile and adult specimens: 61 Gobiodon histrio with total lengths (TL) of 14.9 to 48.3 mm (specimens < 25 mm TL were defined as juveniles), and 32 G. rivulatus with TL of 15.4 to 34.7 mm (specimens < 20 mm TL were defined as juveniles; Dirnwöber & Herler 2007). Traditional measurements were made with a digital sliding caliper to the closest 0.01 mm on ethanol-preserved specimens and included TL (measured from the snout tip to the end of the caudal fin) and greatest head width (gHw, measured at the widest part of the head, which is at the cheek).…”
Section: Fish Morphometric Analysesmentioning
confidence: 99%
“…One of the most compressed species, G. histrio, grows relatively long and exhibits a larger lateral body display compared to congeneric species (Herler & Hilgers 2005, Herler 2007) but can still move easily among the interbranches of its host coral. G. rivulatus, a space competitor of G. histrio, has evolved a different shape to live within the same but also in several other coral species not used by G. histrio (Dirnwöber & Herler 2007). It has a less compressed body and attains a smaller maximum body length.…”
Section: Introductionmentioning
confidence: 99%